Diagnosis of Peritonsillar Abscess—A Prospective Study Comparing Clinical with CT Findings in 133 Consecutive Patients - François Voruz; Rebecca Revol; Christophe Combescure; Yan Monnier; Minerva Becker; Nicolas Dulguerov (Diagnostics)
Background: Peritonsillar abscess (PTA) is relatively common but challenging to diagnose clinically. Several clinical signs may be used, with unknown performances. We evaluated and compared the diagnostic performance of individual and combined clinical signs (trismus, edema, pharynx immobility, uvula deviation, hot potato voice, and overall clinical impression) assessed by an otolaryngologist and of contrast-enhanced computed tomography (CT) to detect acute PTA. Methods: Prospective study in 133 consecutive adult patients (77 males, mean age = 33 years) with suspected clinical PTA and CT obtained in the emergency setting of a tertiary care hospital between November 2020 and October 2022. The standard of reference consisted of surgically proven pus within 24 h of CT or a favorable clinical evolution at 48 h without surgical intervention. Results: PTA was present in 117/133 (88%) patients, with no difference between mean age or sex distribution between the groups with and without PTA. None of the evaluated clinical signs were associated with PTA (OR = 1.26–5.43, p > 0.05), whereas the CT finding “abscess” was significantly associated with PTA (OR = 67.2, p < 0.0001). The sensitivity of individual clinical signs varied between 19.7% and 73.5%, and the sensitivity of CT was significantly higher for all clinical signs (95.7%, p < 0.0001) except for overall clinical impression (97.4%, p = 0.7266). The specificity of clinical signs varied between 12.5% and 93.8%, and the specificity of CT was significantly higher (75%, p < 0.05) for overall clinical impression and edema. All clinical signs together yielded an area under the curve (AUC) = 0.677. Conclusions: In adults, clinical assessment alone using independent clinical signs and overall clinical impression does not allow a reliable diagnosis of PTA, even when performed by an otolaryngologist. CT is reliable in diagnosing PTA and, whenever available, should be the examination method of choice for diagnosing PTA, especially by a non-specialist.